Health status analysis is comparable in HM3 patients with different preoperative grades of mitral regurgitation - Kristin Klaeske; Constantin Schreiber; Sandra Eifert; Tillmann Dieterlen; Khalil Jawad; Diyar Saeed; Sandra Semmig-Könze; Anna Lassia Meyer; Michael Andrew Borger; Maja-Theresa Dieterlen (Journal of Patient-Reported Outcomes, 2023)
Abstract Background The guidelines for mechanical circulatory support of the International Society for Heart and Lung Transplantation do not recommend the routine replacement or repair of the mitral valve at the time point of left ventricular assist device (LVAD) implantation. We investigated different parameters of health status including exercise capacity, anxiety and depression after LVAD implantation in patients with different preoperative grades of mitral regurgitation (MR). Methods A single-center analysis of health status was performed including 45 patients with HeartMate 3 (HM 3) implantation using the 12-items Short Form Health Survey (SF-12) and the Hospital Anxiety and Depression Score (HADS) questionnaires. The study groups were classified according to echocardiographically defined preoperative grade of MR. The group without severe MR comprised 33 patients; the group with severe MR comprised 12 patients. Results Demographic and preclinical characteristics as well as LVAD complications such as thrombosis and bleeding events were comparable between LVAD patients with severe and not severe MR (p > 0.05). Severe MR resolved in all patients after LVAD implantation and improved to moderate, mild or no MR in both groups in a period ranging from 6 months until 2 years. The analyses of SF-12 questionnaire revealed that the physical (p = 0.44) and mental health (p = 0.64) was comparable. The grade of anxiety (p = 0.34) and depression (p = 0.44) was comparable between the groups. Exercise capacity measured by the 6 min walk test correlated positively with the SF-12-determined physical health (p < 0.01, r = 0.518) and negatively with the HADS anxiety (p = 0.01, r = −0.399) and depression (p < 0.01, r = −0.570) scores. Conclusions Our data showed that the health status is comparable in HM 3 patients with different preoperative MR severities in the post-LVAD period. Preoperative severe MR resolves in the majority of patients early after LVAD implantation and is not associated with concomitant mitral valve repair or replacement at the time of LVAD implantation.